The leaking pocket: The implicit struggle for skilled health workers between private not-for-profit and public sector in Tanzania - Isangula, Kahabi G.; Brownie, Sharon (Advances in Social Sciences Research Journal, 2014)
Introduction: Human resource for health is the core building block of an effectively functioning health system, and, competent and motivated health workers are the key drivers at all levels in health service delivery. Public health services in sub-Sahara Africa countries face severe health workforce shortages exacerbated by both outward migration and internal public to private sector migration—Tanzania is no exception. This review was conducted to characterize the extent of health workforce shortages in Tanzania, and the factors impacting on the shortage. Methods: The authors reviewed publicly available data to assess the extent of health workforce shortages within Tanzania and the range of ‘pull’ and ‘push’ factors contributing to the shortages. Results: Findings highlight significant health workforce shortages in Tanzania. Specific ‘pull’ and ‘push’ factors were identified. Pull factors are considered to be factors such as the advantages offered by new jobs, such as higher pay and better working conditions that 'pull' workers towards the new jobs. Push factors have been identified as those negative factors that 'push' workers out of their jobs, such as poor pay, working conditions, and management and governance issues. These factors impact extensively acting upon the recruitment and retention of Tanzanian health workers. The issue of health workforce flow from the public to private not-for- profit sector was particularly notable and the impact this has on the ability to provide an effectively functioning public health system in Tanzania. Conclusion: The authors conclude that opportunities exist for the private not-for- profit sector to take an active role in the production of skilled human resources for health in Tanzania.